The Effect of Income Levels and Notification of Tax Payable (SPPT) on Taxpayer Compliance in Paying Land and Building Taxes (A Case Study in the Cinere District of Depok City) - Siti Nurkayatin; Juitania Juitania (IDEAS: Journal of Management & Technology, 2022)
This study aims to empirically examine the effect of income levels and tax returns payment revenue (SPPT) on taxpayer compliance in paying land and building taxes in Cinere District. The research method used is quantitative descriptive research. The technique for determining the sample of this study used a random sampling technique by distributing questionnaires to 400 respondents who had been calculated using the Slovin formula. The data analysis method used is descriptive statistical analysis test, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test (R2), simultaneous test (F), and partial test (t). The data processing used SPSS data processing program version 23. Based on the simultaneous analysis it can be concluded that there is a significant influence between income level variables and tax returns payment revenue (SPPT) on taxpayer compliance in paying land and building taxes in Cinere District. Based on the partial analysis, it can be concluded that the income level variable had a significant effect on taxpayer compliance and the variable tax returns payment revenue (SPPT) had a significant effect on taxpayer compliance in paying land and building taxes in Cinere District.